The use of sport and the Olympic values as a social policy tool, creating apositive impact for under-privileged communities - Cea Zamayoa, Regina Patricia (Πανεπιστήμιο Πελοποννήσου, 2021)
The purpose of the main study is to explore the use of sport and the Olympic values as a social policy for the development of under-privileged communities basing the study on the Sport for Development and Peace approaches by considering the IOC main purpose “Olympism is a philosophy of life, exalting and combining in a balanced whole the qualities of body, will and mind, blending sport with culture and education, Olympism seeks to create a way of life based on the joy found in effort, the educational value of good example and respect for universal fundamental ethical principles.” Drawing a qualitative study utilizing the IOC programme better known as “Sport for hope” which takes place in the countries of Zambia and Haiti, consisting on interviews to the IOC like the Head of the programme Barbara Schweizer Senior Sport for Development Program Manager of public Affairs and Social Development through Sport, as based at the UNESCO “Sport for Development and Peace proponents, not only but also the investigation consists in different case studies which help demonstrate the benefits of sport programmes for under developed communities such as Skateistan in which Jessica Falukner Communication Manager of the NGO has been interviewed as well as the help of Lissane Comeau Senior Program Director of Shooting Touch which takes place in Africa as in the Unite States of America.
Keywords: Olympism; Olympic movement; Olympic education - Curriculum; Olympics - Social aspects; Ολυμπισμός; Ολυμπιακό κίνημα; Ολυμπιακή παιδεία - Πρόγραμμα μαθημάτων; Ολυμπιακοί αγώνες - Κοινωνικές απόψεις; Olympic values; Cohersion; Policy; Sport; Development